2019
DOI: 10.1098/rsos.190952
|View full text |Cite
|
Sign up to set email alerts
|

Salting-out assisted liquid–liquid extraction coupled with high-performance liquid chromatography for the determination of vitamin D3 in milk samples

Abstract: In this study, salting-out assisted liquid–liquid extraction (SALLE) as a simple and efficient extraction technique followed by high-performance liquid chromatography (HPLC) was employed for the determination of vitamin D3 in milk samples. The sample treatment is based on the use of water-miscible acetonitrile as the extractant and acetonitrile phase separation under high-salt conditions. Under the optimum conditions, acetonitrile and ammonium sulfate were used as the extraction solvent and salting-out agent, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…6), which indicated that the extraction method influenced the salting-out efficiency of solamargine and solasonine from the aqueous solution in the presence of NaCl or Na 2 CO 3 . The effect of extraction conditions on salting-out was also reported by Tajeda-Casado et al [20] and Sazali et al [21]. The doubly charged carbonate ions from Na 2 CO 3 interacted with the hydration sphere surrounding the solute (solamargine and solasonine) to a greater extent than singly charged chloride ions from NaCl, forming carbonic acid.…”
Section: Ma-atpesupporting
confidence: 67%
See 1 more Smart Citation
“…6), which indicated that the extraction method influenced the salting-out efficiency of solamargine and solasonine from the aqueous solution in the presence of NaCl or Na 2 CO 3 . The effect of extraction conditions on salting-out was also reported by Tajeda-Casado et al [20] and Sazali et al [21]. The doubly charged carbonate ions from Na 2 CO 3 interacted with the hydration sphere surrounding the solute (solamargine and solasonine) to a greater extent than singly charged chloride ions from NaCl, forming carbonic acid.…”
Section: Ma-atpesupporting
confidence: 67%
“…Aqueous two-phase extraction (ATPE) is desired for its environmental compatibility, low interfacial tension of phases, high yields, and low process time [17,18]. Recently, researchers have turned their attention to an improved version of ATPE, salting-out assisted liquid-liquid extraction (SALLE) technique, which facilitates extraction of metabolites from complex matrices [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the extent of salting out was further driven by the increase in mass of plant powder due to mass transfer under the conditions studied. The salting-out effect in ATPE was also reported by Sazali et al (2019) and Mokgehle et al (2021). Additionally, the higher extraction of solasodine via Na 2 CO 3 compared to NaCl can correlates with the Hoffmeister series.…”
Section: Chromatographic Pro Le Of Mrm Based Quanti Cation Of Solasodinesupporting
confidence: 57%
“…Salting-out is an effective pre-concentration method which has been studied for the extraction of Vitamin D3 in milk samples [26] partitioning of biomolecules [56] and determination of 5-nitroimidazolesin in fish [21]. Salting-out is dependent on the nature of the salt involved.…”
Section: Mass Spectra Of Alkaloid Derivativesmentioning
confidence: 99%
“…This method uses solvents such as ethanol (EtOH) or acetonitrile (MeCN), as extraction solvents because water-solubility is minimized when salts are added to samples and extraction media [20,21]. The SALLE procedure has been widely applied for extraction of compounds from various matrices because of its simplicity and effectiveness [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%